ANALISIS PENERAPAN METODE PEMBERIAN TUGAS PADA MATA PELAJARAN EKONOMI KELAS XI IIS3 - Nuriansyah Nuriansyah; Sulistyarini Sulistyarini; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research aims to determine the implementation of the assignment method in economic subjects in class XI IIS3 SMA Negeri 1 Jawai. The research method used is a descriptive method with a qualitative approach and a form of survey research. The data in this study were 1 teacher of class XI IIS3 economics class at SMA Negeri 1 Jawai and 3 students of class XI SMA Negeri 1 Jawai from class XI IIS3 SMA Negri 1 Jawai. Data collection was obtained through observation guidelines and interview guidelines then analyzed using data reduction, data presentation and verification / conclusion, then the validity of the data used technical triangulation. Researchers conducted research with research observations 3 times and interviews for 1 day. The results showed that the implementation of the assignment method in economic subjects in class XI IIS3 SMA Negeri 1 Jawai was good from preliminary activities, core activities and closing activities. So the implementation of the application of the assignment method to economic subjects in class XI IIS3 SMA Negeri 1 Jawai is overall good.Keywords: Implementation, Assignment, Economic Lessons